Ethno-STEM-Based Science Learning Using Typical Foods of Sidoarjo to Improve Science Literacy among Junior High School - Regina Atya Gading Balgis Solikha; Noly Shofiyah (APPLICATION: Applied science in Learning Research, 2025)
The low level of science literacy among junior high school students indicates the need for contextual and meaningful learning. Therefore, this research aims to determine the effect of Etno-STEM-based science learning on Sidoarjo's typical foods on junior high school students' science literacy. This research used a one-group pretest-posttest design with purposive sampling. The subjects of this study were 20 eighth-grade students at a junior high school in Sidoarjo Regency. The research instrument consisted of 15 multiple-choice questions based on three indicators of science literacy, namely explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and evidence scientifically. The pretest and posttest data were analyzed using the N-Gain test and paired t-test to determine the level of improvement and the significance of the difference in students' science literacy skills. The N-Gain analysis showed a value of 0.89 for the indicator of explaining phenomena scientifically, 0.79 for the indicator of evaluating and designing scientific investigations, and 0.78 for the indicator of interpreting data and evidence scientifically. All three values were in the high category, indicating an improvement in students' science literacy skills. These findings were reinforced by the results of the paired t-test, which showed a significance value of < 0.05, so it can be concluded that Etno-STEM-based science learning using Sidoarjo's typical foods had a significant effect on students' science literacy.